Osteochondral Autograft Transfer for Capitellar Chondral and Osteochondral Defects - Shiv P. Patel, M.D., M.S.; Ryan T. Conyer, M.D.; Theodore B. Shybut, M.D. (Arthroscopy Techniques, 2020)
Chondral and osteochondral lesions of the humeral capitellum, most notably osteochondritis dissecans, most commonly present in adolescent baseball players and gymnasts. A variety of surgical techniques can be used to address these lesions. Osteochondral autograft transfer has recently shown superior rates of return to sport. We describe osteochondral autograft transfer from the contralateral knee to treat a large full-thickness chondral lesion of the humeral capitellum. Osteochondral allograft backfill of the donor site is shown as well. This surgical procedure is technically demanding but very reproducible and maximizes return to play in patients while minimizing donor-site morbidity.